2006
DOI: 10.1104/pp.106.086835
|View full text |Cite
|
Sign up to set email alerts
|

Natural Experiments Indicate That Geomagnetic Variations Cause Spatial and Temporal Variations in Coconut Palm Asymmetry

Abstract: In plants with alternately arranged foliage, such as the coconut palm (Cocos nucifera), leaves are attached to the stem in either an ascending clockwise (left handed [L]) or counterclockwise (right handed [R]) spiral (Fig. 1). Foliar spiral direction (FSD) is not genetically determined in coconut palms: All crosses (R 3 R, R 3 L, L 3 R, L 3 L) yield R and L progeny in approximately equal numbers (Davis, 1962;Louis and Chidambaram, 1976;Toar et al., 1979). FSD is, thus, a classic case of morphological asymmetry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Based on these findings, Minorsky (1998) proposed that asymmetries in coconut palm FSD result from the Earth currents induced by variations in the vertical Z component of the geomagnetic field that cause a rotational bias in the axial migration of morphogens (e.g., auxin transporters) in coconut palm embryos. Minorsky and Bronstein (2006) presented two new lines of evidence that geomagnetic variations may underlie asymmetries in coconut palm FSD. First, they showed that asymmetries occur in the FSD of palm populations on opposite sides of islands, and second, that asymmetries in FSD vary with the sunspot cycle.…”
Section: Effects Of Geomagnetic Storms On Plantsmentioning
confidence: 97%
See 4 more Smart Citations
“…Based on these findings, Minorsky (1998) proposed that asymmetries in coconut palm FSD result from the Earth currents induced by variations in the vertical Z component of the geomagnetic field that cause a rotational bias in the axial migration of morphogens (e.g., auxin transporters) in coconut palm embryos. Minorsky and Bronstein (2006) presented two new lines of evidence that geomagnetic variations may underlie asymmetries in coconut palm FSD. First, they showed that asymmetries occur in the FSD of palm populations on opposite sides of islands, and second, that asymmetries in FSD vary with the sunspot cycle.…”
Section: Effects Of Geomagnetic Storms On Plantsmentioning
confidence: 97%
“…More recently, Minorsky and Bronstein (2006), studying coconut palms, have presented evidence that geomagnetic storms may affect another process in plants, namely the manner in which leaves are attached to the stem. In coconut palms, leaves are attached to the stem in either a left-handed (L) or right-handed (R) spiral.…”
Section: Effects Of Geomagnetic Storms On Plantsmentioning
confidence: 97%
See 3 more Smart Citations